Comparison of invasive blood pressure monitoring vs. non-invasive blood pressure monitoring in critically ill children receiving vasoactive agents—a prospective observational study - Shah, Sachin; Kaul, Amita; Nagarkar, Rohini; Thorat, Amol (Frontiers in Pediatrics, 2024)
Objective: The primary aim of this study was to compare non-invasive blood pressure (NIBP) measurement using the automated oscillometric method with invasive blood pressure (IBP) measurement using peripheral arterial line insertion in critically ill children receiving vasoactive agents. Design: Single-centre, prospective cohort study. Setting: Tertiary care 15 bedded Pediatric ICU in Urban Indian city Subjects: All critically ill children between the ages of 1 month to 16 years with shock on vasoactive medications and with IBP monitoring. Intervention: None Measurements and main results: Forty children with 1072 paired BP measurements were incorporated in the final analysis. Among all normotensive children (Total number of paired measurements = 623) receiving vasoactive agents, Bland–Altman analysis revealed an acceptable agreement between Invasive mean blood pressure (MBP) and non-invasive MBP with a bias of -2.10 mmHg (SD 11.35). The 95% limits of agreement were from -24.34 to 20.14 mmHg. In children with hypotension (Total number of paired measurements = 449), Bland–Altman analysis showed disagreement between Invasive MBP and non-invasive MBP i.e., a bias of -8.44 mmHg (SD 9.62). The 95% limits of agreement were from -27.29 to 10.41 mmHg. Conclusion: A limited agreement exists between invasive blood pressure (IBP) and non-invasive blood pressure (NIBP) measurements in critically ill children requiring vasoactive agents. This discrepancy can lead to either an underestimation or an overestimation of blood pressure. While NIBP can serve as a screening tool for hemodynamically stable children, those who are hemodynamically unstable and necessitate the initiation of vasoactive agents should undergo IBP monitoring.